WATER USAGE ACCORDING TO THE CONCESSION MODEL ACCORDING TO THE LAW OF THE REPUBLIC OF SRPSKA - Čubrilović Stamenić, Bosiljka (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2023)
The author's interest in water usage according to the concession model in domestic legislation was aroused by the Decision of the Constitutional Court of Bosnia and Herzegovina in Case No. U-16/20. The analysis of the above decision has opened up a wider space for thinking, and the presented article was created due to research in this area. The paper is methodologically based on the normative analysis of the Law on Concessions and the Real Right Law, which is an umbrella legislative act when discussing real law institutes in the Republic of Srpska. Although in the first part of the paper we dealt with the special legal regulation of certain types of things and defining the concepts of water, water assets and water objects, as the subject of property rights, the focus of the paper is still relevant issues related to water, as the subject of a concession. The subject of the concession can be the right to perform a wide range of economic activities, and when it comes to water, it is most often about the use of public water assets (water for technological processes in the performance of economic activities, water and water land for the use of hydro reservoirs, swimming pools, ponds, water land for the realization of some of the economic activities, as well as the extraction of materials from watercourses). In addition, the energy potential of water can be used when the concession object is the construction and use of energy plants, as one of the most important economic aspects of water exploitation. In the last part of the work, the practice of the Constitutional Court about the institute of concessions, but also a broader issue that is increasingly emphasized in domestic jurisprudence, is discussed, which is the concept of "state property".
Keywords: concession; water; BOT model; “state property”; public property